2019
DOI: 10.2174/0929867324666170515123807
|View full text |Cite
|
Sign up to set email alerts
|

Food and Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux disease is a chronic condition with a high prevalence in western countries. Transient lower esophageal sphincter relaxation episodes and a decreased lower esophageal sphincter pressure are the main mechanisms involved. Currently used drugs are efficient on reflux symptoms, but only as long as they are administered, because they do not modify the reflux barrier. Certain nutrients or foods are generally considered to increase the frequency of gastroesophageal reflux symptoms, therefore ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 79 publications
1
38
0
7
Order By: Relevance
“…Specifically, foods with a high fat content have been shown to increase the number of GERD episodes significantly when compared to foods with normal fat content . Similarly, spicy food may induce heartburn, but the literature is not conclusive . Culinary differences across the country, such as the popularity of spicy and deep fried foods in the South, could contribute to regional variability in risk factors and subsequent prescribing differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, foods with a high fat content have been shown to increase the number of GERD episodes significantly when compared to foods with normal fat content . Similarly, spicy food may induce heartburn, but the literature is not conclusive . Culinary differences across the country, such as the popularity of spicy and deep fried foods in the South, could contribute to regional variability in risk factors and subsequent prescribing differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…Regular intake of chocolate induces the gastric acid reflux with increasing lower esophageal exposure to acid. Spicy foods might as well induce heartburn, but the mechanism has not known yet [ 34 ]. The consumption of fast food is considered as a risk factor for acid reflux [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain nutrients such as fat intake as well as food such as lemons or orange juice, spicy food, garlic, coffee, and alcohol have been thought to increase the frequency of GERD symptoms . We found that nGER symptoms became more severe with more frequent high‐fat diet and carbonated beverages.…”
Section: Discussionmentioning
confidence: 66%